SELF-ASSESSMENT OF LATVIAN SUPERVISORS’ DIGITAL COMPETENCE - Bergmane, Tatjana; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The importance of digital competence (Dc) is significantly increasing as global digital transformation continue rapidly to develop and digital solutions are extensively integrating into all areas.  As a result, Dc is included as one of eight core competences for lifelong learning. The present study aimed to find out the self-assessment of the importance (an assessment of how significant and necessary a certain value is) and attainability (an assessment of how attainable a certain value is) of Latvian supervisors’ Dc. Digital competence self-assessment questionary is theoretically based on a major European Union research project, DigComp 2.1 and identifies the key components of Dc in 5 areas, namely, information and data literacy, communication and collaboration, digital content creation, safety and problem solving. 56 respondents participated in the online survey during October 2021. The importance and attainability indicators of Dc statements were evaluated on a 5-point Likert scale. The study indicated rather high importance of Dc (3 of 51 statements were evaluated as very important, 43 as rather important and 5 as moderately important). The indicators of the attainability of Dc varied from rather unattainable to rather attainable (26 of 51 statements were evaluated as rather attainable, 21 as average attainable and 4 as rather unattainable). Wilcoxon signed-rank test indicated statistically significant differences in 34 out of 51 statements of Dc that was evaluated higher in importance than attainability. The study results show high level of supervisors’ awareness of the digital competence importance. The obtained attainability results allowed to highlight the need for the further digital competence improvement for the supervisors, especially at such digital competence areas as safety and problem solving.